Filsafat Ilmu Imre Lakatos dan Metodologi Pengembangan Sains Islam - Mohammad Muslih (Tasfiyah: Jurnal Pemikiran Islam, 2020)
This paper will discuss Imre Lakatos’ thought on research methodology which has been successful to reunite fundamental thought of Popper’s falsification and Kuhn’s paradigm shif and to make both of them being able to be used as scientific method to develop science at once. Exactly, this effort has a great contribution toward developing the philosophy of science because it is not only confirming that developing science should be done collaboratively and sustainably but also offering the method to make it happen. Furthermore, Lakatos’ offer provides “undeniable” assumption called “the hard core” as inseparable part of “scientific building”. This so-called the hard core has made Islamic science, which is based on religion, could be not only developed but also has found its foundation of methodology.